The Role of the Village Government to Increase Community Participation in Village Development (Study in Sidorejo Village, Jabung District, Malang Regency) - Sigit Wahyudi; Sulafah Fathin Khannanah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research was conducted because the participation of the community in Sidorejo Village, Jabung District, Malang Regency in the Covid-19 pandemic era became important. The Covid-19 pandemic had a significant impact on Sidorejo Village, such as many people who lost their jobs and unemployment which resulted in reduced community income. Therefore, the role of the village government to increase community participation in village development must also be carried out with the aim of restoring the level of the economy and community participation in village development as before the Covid-19 pandemic. This study aims to identify, describe and analyze the role of the village government in increasing community participation in village development (Study in Sidorejo Village, Jabung District, Malang Regency) and what challenges the village government faces in increasing community participation in the village. Development in Sidorejo Village, Jabung District, Malang Regency. This research uses descriptive research with a qualitative approach. Data analysis used data analysis methods from Miles, Huberman and Saldana (Miles, Huberman and Saldana, 2014). The results of this study indicate that the role of village government in village development can be said to be successful, by applying several village management principles. Although there was still community participation after the coaching, they did not follow up on the results of the coaching. So that in this study it can be seen that several elements are also obstacles in increasing community participation in the development of Sidorejo village. There are several inhibiting factors that cause some elements have not been maximized or achieved. These factors can come from internal and external. The success of the development of Sidorejo Village cannot be separated from the cooperation between stakeholders involved in village development.